Stable DNA methylation boundaries and expanded trinucleotide repeats: role of DNA insertions - Naumann, Anja; Kraus, Cornelia; Hoogeveen, Andre; Ramirez, Christina M.; Dörfler, Walter (Journal of Molecular Biology, 2014)
The human genome segment upstream of the FMR1 (fragile X mental retardation 1) gene (Xq27.3) contains several genetic signals, among them is a DNA methylation boundary that is located 65-70 CpGs upstream of the CGG repeat. In fragile X syndrome (FXS), the boundary is lost, and the promoter is inactivated by methylation spreading. Here we document boundary stability in spite of critical expansions of the CGG trinucleotide repeat in male or female premutation carriers and in high functioning males (HFMs). HFMs carry a full CGG repeat expansion but exhibit an unmethylated promoter and lack the FXS phenotype. The boundary is also stable in Turner (45, X) females. A CTCF-binding site is located slightly upstream of the methylation boundary and carries a unique G-to-A polymorphism (single nucleotide polymorphism), which occurs 3.6 times more frequently in genomes with CGG expansions. The increased frequency of this single nucleotide polymorphism might have functional significance. In CGG expansions, the CTCF region does not harbor additional mutations. In FXS individuals and often in cells transgenomic for EBV (Epstein Barr Virus) DNA or for the telomerase gene, the large number of normally methylated CpGs in the far-upstream region of the boundary is decreased about 4-fold. A methylation boundary is also present in the human genome segment upstream of the HTT (huntingtin) promoter (4p16.3) and is stable both in normal and Huntington disease chromosomes. Hence, the vicinity of an expanded repeat does not per se compromise methylation boundaries. Methylation boundaries exert an important function as promoter safeguards.
EVALuna2:8223